Civil society and community based organizations in the trincomalee district in relation to women with disabilities - Gonsalkorala, L.R.; Kusumawathie, N.G.; Premathilaka, C.K. (University of Jaffna, 2012)
About 650 million people in the world live with disabilities and frequently encounter physical and social obstacles. They often lack opportunities of the mainstream population and are usually among the most marginalized in society. Persistence of cultural, legal and institutional barriers make women with disabilities the victims of two fold discriminations: as women and as persons with disabilities. They are ignored and discriminated by non-governmental organizations and even by womens’ movements. However, they are in need of support and recognition from the governments as well as from other various organizations existing in the society. Various organizations the world over strive to assist persons with disabilities to overcome the obstacles they face. The Abaditha Kantha Sangamaya based at Anuradapura, Sri Lanka is one of them. The aim of the study was to collect information about the civil society and community based organizations in relation to women with disabilities in the Trincomalee district. The objectives were to investigate the awareness of those organizations about women with disabilities, identify the assistance that could be given to them by the organizations and to find out whether training is needed for the organizations to provide such assistance. The design of the study was the descriptive survey design and a sample of 50 civil society and community based organizations were selected. A questionnaire was used to collect data. The majority of the organizations were not aware about the legislations/conventions related to disabled persons. Almost all organizations were willing to provide assistance to women with disabilities in various ways. Prominent among them were providing loans, equipment, health services and counselling, developing vocational skills, raising awareness and empowerment. Only a very small number of organizations had received some sort of training related to disabled persons but all organizations expressed willingness to participate in training and also to share the knowledge with others. It is recommended that awareness raising programmes on the rights of women with disabilities should be conducted for such organizations. And their training needs in providing assistance to women with disabilities should be fulfilled.